CGIAR Research Program on Grain Legumes and Dryland Cereals - Plan of Work and Budget 2021 - CGIAR Research Program on Grain Legumes and Dryland Cereals (CGIAR Research Program on Grain Legumes and Dryland Cereals, 2021)
The ToC for FP1 and FP3 remain largely unchanged and the team is making efforts to ensure that progress is being made towards the set outcome targets. Together with the cross-cutting themes, FP4 uses CRP experiences to develop a more detailed and impactful ToC by identifying enablers that allow FP4 innovations to unfold their full potential. While there is no major update in the ToC of FP5, work will be done along with other FPs to incorporate FP6 into the CRP-GLDC’s overall ToC. The FP6’s ToC will remain unchanged in 2021.